Assesment Schedule Metode Defense Contract Management Agency (DCMA) Menggunakan Software Primavera P6 Studi Kasus Proyek Jembatan - Ranto Tumangger; Agustina, Resti (Politeknik Negeri FakFak, 2026)
Project scheduling is a critical aspect of ensuring the successful implementation of construction projects, particularly bridge projects that involve a high degree of complexity. Poor schedule quality may result in project delays, inaccurate critical path identification, and inadequate project control. This study aims to evaluate the schedule quality of a pile slab bridge project using the Defense Contract Management Agency (DCMA) 14-Point Schedule Assessment method, supported by Oracle Primavera P6 software. The study employed a quantitative descriptive method with a case study approach applied to an existing baseline schedule. The assessment results indicate that several parameters have satisfied the DCMA standards, including relationship type, hard constraints, soft constraints, negative float, large duration, and invalid progress. Conversely, several parameters remain non-compliant with the established standards, namely network logic, positive lag, large float, resources/cost, and the Baseline Execution Index (BEI). This study concludes that the project schedule has not fully adhered to the principles of a network-driven schedule and continues to function primarily as an administrative time schedule. The findings of this study offer practical contributions to construction project management by providing recommendations that encompass the refinement of network logic relationships, reduction of excessive lag usage, implementation of resource and cost loading, and progress updates based on the established baseline, thereby enabling the schedule to serve as a more effective, reliable, and integrated project control tool